Poetry: Therapeutic Functions and Effects on Youth Mental Well-being in Post-COVID -19 Era in Nigeria - Awodiya, Esther Funke; Fajobi, Tolulope Adetayo; Ademowo, Adeyemi Johnson (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Poetry is a form of positive distraction for youths that can improve mental well-being. During stress, trauma, and grief, poetry writing helps put thoughts together. The COVID-19 lockdown period gave rise to many artistic expressions from the youth. This form of engagement continued during the post-COVID Period, which led to increased numbers of active participants in poetry writing and literary organizations activities in Nigeria. This paper examines the experiences of youth involved in poetry writing during and after the COVID lockdown in Nigeria. It also explores the perceived contribution of poetry writing to mental well-being of youth. However, there are young people who write poetry who died by suicide, using their poems as an outlet before their death. The study adopts a descriptive research design through a qualitative approach, and the data were sourced through secondary data and interviews. The theoretical framework for this paper is the social action theory. The research established that poetry is therapeutic in nature. It helps to deal with difficult circumstances. Youths interviewed associate positive feeling to poetry writing. But the research found that literary engagement and group activities contribute to mental well-being too. This study, thus, recommends that more scholarly attention should be directed to literary hubs and their contribution of mental well-being of youth.